Progress of HL-2A experiments and HL-2M program. (1st April 2022) - Duan, X.R.; Xu, M.; Zhong, W.L.; Liu, Y.; Song, X.M.; Liu, D.Q.; Wang, Y.Q.; Lu, B.; Shi, Z.B.; Zheng, G.Y.; Liu, Yong; Yang, Q.W.; et al.
Abstract: Since the last IAEA Fusion Energy Conference in 2018, significant progress of the experimental program of HL-2A has been achieved on developing advanced plasma physics, edge localized mode (ELM) control physics and technology. Optimization of plasma confinement has been performed. In particular, high- β N H-mode plasmas exhibiting an internal transport barrier have been obtained (normalized plasma pressure β N reached up to 3). Injection of impurity improved the plasma confinement. ELM control using resonance magnetic perturbation or impurity injection has been achieved in a wide parameter regime, including types I and III. In addition, impurity seeding with supersonic molecular beam injection or laser blow-off techniques has been successfully applied to actively control the plasma confinement and instabilities, as well as plasma disruption with the aid of disruption prediction. Disruption prediction algorithms based on deep learning are developed. A prediction accuracy of 96.8% can be reached by assembling a convolutional neural network. Furthermore, transport resulting from a wide variety of phenomena such as energetic particles and magnetic islands has been investigated. In parallel with the HL-2A experiments, the HL-2M mega-ampere class tokamak was commissioned in 2020 with its first plasma. Key features and capabilities of HL-2M are briefly presented.